Symptomatic Cholelithiasis in a Male Infant: Two-Year Follow-Up and Surgical Management – A Case Report - Manuel Gonzalez Plascencia; Antonio Ignacio del Rio Robles (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Infant cholelithiasis is an uncommon and often idiopathic condition, frequently detected incidentally due to nonspecific symptoms. Although spontaneous resolution is common during infancy, the lack of standardized management guidelines complicates decision-making, particularly in symptomatic patients. Long-term data describing the natural history and indications for surgical intervention remain limited. Case: We describe a male infant diagnosed with gallstones at four months of age following recurrent episodes of colicky abdominal pain. Extensive laboratory evaluation excluded hemolytic, metabolic, infectious, and anatomical causes. Serial ultrasonography confirmed persistent gallstones without inflammatory changes. Given the patient’s clinical stability, expectant management with close follow-up was initially chosen, including periodic clinical assessments, annual ultrasound examinations, and biochemical testing. Despite normal growth and normal biochemical results, the patient experienced intermittent recurrent localized abdominal pain over a two-year period. Because of persistent symptoms, definitive surgical management was indicated, and an open cholecystectomy was performed at two years of age. Intraoperative findings revealed two black pigment stones consisting of calcium bilirubinate, without anatomical abnormalities. Postoperative recovery was uneventful, and the patient remained asymptomatic during follow-up. Discussion: This case illustrates the challenges of managing idiopathic infant cholelithiasis, particularly regarding the timing of surgery. While conservative management is appropriate for asymptomatic patients, persistent or recurrent symptoms justify surgical intervention. This extended follow-up provides insight into the persistence of the disease beyond infancy. Conclusion: Individualized management is essential in infant cholelithiasis. This case supports surgical treatment in symptomatic patients with persistent gallstones, even in the absence of identifiable risk factors.